The Typology of Sabdopalon Innovation in Kedunglosari Village Tembelang Sub-District Jombang Regency - Vega, Berinda; Rohman, Hermanto; Pamungkas, Tree Setiawan (Universitas Muhammadiyah Sidoarjo, 2024)
One of the most important processes in efforts to realize improvements in the quality of public services is to carry out breakthrough innovations. The existence of statutory regulations governing regional innovation is a reference for Regional Governments to carry out innovations to improve the quality of public services. The Sabdopalon innovation is one of the public service innovations in Jombang Regency which is useful for improving the quality of electronic-based Village Government services by integrating several service scopes. This research aims to determine innovation and innovation typology based on the theory of Halvorsen, et al. (2005) in Kedunglosari Village, Tembelang District, Jombang Regency. This research uses a positivistic research approach with the type of research used is descriptive research and the data analysis used is qualitative. The research results show that the Sabdopalon innovation (Sistem Administrasi Berita Data Deso dan Pelayanan Online) is a manifestation of the Jombang Regency Smart City Masterplan in the public sector which involves the village government as the lowest level agency that is integrated with Jombang Regency government agencies. The Sabdopalon innovation in Kedunglosari Village, Tembelang District, Jombang Regency is by the six innovation typologies presented by Halvorsen, et al. (2005).